ANALISIS POLITICAL CONNECTION, FAMILY OWNERSHIP DAN MANAGERIAL OWNERSHIP TERHADAP EARNINGS MANAGEMENT - Jonathan, Stevanus; Lukman, Hendro; Verawati, Verawati (Jurnal Paradigma Akuntansi, 2025)
This study aims to analyze the influence of political connections, family ownership, and managerial ownership on earnings management in mining companies listed on the Indonesia Stock Exchange for the period 2017 – 2021. The method used in this research is a quantitative method with purposive sampling. The sample data used are 41 data from 11 mining companies. The collected sample data was processed using multiple regression analysis tests and assisted by IBM SPSS Statistics version 29 software. The results of this study are political connections and family ownership do not have a significant effect on earnings management, while managerial ownership has a significant influence on earnings management. The implication of this research is that shareholders must increase management or agent supervision, including as managerial ownership of earnings management practices that do not harm the company.